Squaramides as novel class I and IIB histone deacetylase inhibitors for topical treatment of cutaneous t-cell lymphoma. Issue 17 (15th September 2018) - Fournier, Jean-François; Bhurruth-Alcor, Yushma; Musicki, Branislav; Aubert, Jérome; Aurelly, Michèle; Bouix-Peter, Claire; Bouquet, Karinne; Chantalat, Laurent; Delorme, Marion; Drean, Bénédicte; Duvert, Gwenaelle; Fleury-Bregeot, Nicolas; et al.
Graphical abstract: Highlights: A novel squaramide-based scaffold for HDAC inhibition is proposed. Inhibitors are optimized for topical route of administration. Aqueous and organic solubility is optimized by crystal lattice perturbation. Optimized HDAC inhibitors are class I, IIB and IV selective. Abstract: A series of squaramide-based hydroxamic acids were designed, synthesized and evaluated against human HDAC enzyme. Squaramides were found to be potent in the Hut78 cell line, but initially suffered from low solubility. Leads with improved solubility and metabolic profiles were shown to be class I, IIB and IV selective.